Entrepreneurial Framework Conditions and Economic Growth: Insights from Middle-Income Economies - Frank Ranganai Matenda; Justin Chirima; Mabutho Sibanda (Acta Economica)
This article implements correlation analysis and a fixed effects model to assess the influence of entrepreneurial framework conditions (EFCs) on economic growth in middle-income countries. The implemented panel data set for EFCs is unearthed from the Global Entrepreneurship Monitor website and that for gross domestic product (GDP) per capita, a surrogate for economic growth, is extracted from the World Bank website over the observation period 2001 – 2021. We have discovered that there are statistically significant positive correlations between GDP per capita and ‘entrepreneurial finance’ and ‘post-school entrepreneurial education and training’, and statistically significant negative correlations between GDP per capita and ‘taxes and bureaucracy’, ‘internal market openness’, and ‘physical and service infrastructure’. Moreover, we have exposed that EFCs positively and significantly impact economic growth in middle-income countries. This article contributes to the discourse on the connection between economic growth and conditions for entrepreneurship in middle-income economies. As a recommendation, policymakers should consider EFCs when developing policies to kindle economic growth in middle-income economies. Further, the study results could assist policymakers in selecting and applying suitable measures to eradicate the impediments in the businesses where entrepreneurs operate.